2012
DOI: 10.2174/156652312800840559
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stem Cells in Muscular Dystrophies

Abstract: Muscular dystrophies are heterogeneous neuromuscular disorders of inherited origin, including Duchenne muscular dystrophy (DMD). Cell-based therapies were used to promote muscle regeneration with the hope that the host cells repopulated the muscle and improved muscle function and pathology. Stem cells were preferable for therapeutic applications, due to their capacity of self-renewal and differentiative potential. In the last years, encouraging results were obtained with adult stem cells to treat muscular dyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 134 publications
(175 reference statements)
0
12
0
2
Order By: Relevance
“…62 The identification of a stem cell population providing efficient muscle regeneration is critical for the progression of cell therapy for muscle diseases. 63 Despite early data reporting AFS cell capacity of expressing molecular markers of muscle differentiation under specific culture conditions, 35 high impact papers have just been very recently published. First, Gekas et al 48 demonstrated that human, 2nd trimester, CD117 + -selected AFS cells can acquire a myogenic-like phenotype (i.e., expression of desmin and MyoD) after culture in myogenic-specific induction conditions (i.e., culture on plastic plates coated with Matrigel and 3 mM 5-aza-2'-deoxycytidine).…”
Section: Cd117+ Amniotic Fluid Stem Cellsmentioning
confidence: 99%
“…62 The identification of a stem cell population providing efficient muscle regeneration is critical for the progression of cell therapy for muscle diseases. 63 Despite early data reporting AFS cell capacity of expressing molecular markers of muscle differentiation under specific culture conditions, 35 high impact papers have just been very recently published. First, Gekas et al 48 demonstrated that human, 2nd trimester, CD117 + -selected AFS cells can acquire a myogenic-like phenotype (i.e., expression of desmin and MyoD) after culture in myogenic-specific induction conditions (i.e., culture on plastic plates coated with Matrigel and 3 mM 5-aza-2'-deoxycytidine).…”
Section: Cd117+ Amniotic Fluid Stem Cellsmentioning
confidence: 99%
“…Continuous cycles of degeneration and regeneration of muscle fibers exhausts the muscle stem cell pool, leading to muscle being replaced by adipose and fibrotic tissue. Stem cell therapy holds great promise as a treatment for Duchenne muscular dystrophy by providing cells that can both deliver functional muscle proteins and replenish the stem cell pool [72].…”
Section: Stem Cell Therapy In Duchenne Muscular Dystrophymentioning
confidence: 99%
“…69 In recent years, a number of tissue-specific adult stem cells, which maintain, generate, and replace terminally differentiated cells within their resident organ, have demonstrated myogenic potential. 53 Among the most promising are adult MSCs, which can differentiate to form myogenic cells in situ. 20 In contrast to other DMD cell-based therapies, MSCs also possess distinct anti-inflammatory activities and represent an ethical alternative to ES cells.…”
Section: Pluripotent and Non-muscle-derived Progenitor Cellsmentioning
confidence: 99%